Blackthorn - Geissinger, J. T. (Bramble/Tor Publishing Group, 2025)
"Blackthorn is a dark gothic romance by New York Times bestselling author J.T. Geissinger. You never forget your first love. Twelve years ago, Maven Blackthorn fled her small hometown, leaving behind the wreckage of her mother's suspicious death. In New York City, she built a new life -- one without the shadows of the past and the whispers of "witch" that always haunted her. But now, drawn back for her grandmother's funeral, Maven and her daughter, Bea, step onto Blackthorn soil once more, only to find themselves thrust into a fresh nightmare: her grandmother's body has vanished. The Blackthorns immediately suspect the Crofts -- the ruthless titans of Croft Pharmaceuticals, whose bitter blood feud with the Blackthorns has spanned generations. But when Maven comes face-to-face with Ronan Croft, the son of her mother's suspected killer and the only man she ever loved, the past and present collide with explosive consequences. As long-buried family secrets claw their way to the surface, betrayal lurks behind every whisper, and old vendettas ignite anew. The deeper Maven digs for answers, the more dangerous the game becomes. And in a town where the dead won't stay buried, neither will the truth -- no matter who it destroys. Blackthorn is a page-turning gothic romance with darker themes and scenes that may not be suitable for everyone. *Revenge *Touch her and die *Shadier than shade hero *Forbidden romance *Grumpy/grumpy *Plot twists galore *Beauty and the Beast *Enemies to lovers to enemies to...?" --